Pendidikan Konservasi Perspektif Warisan Budaya Untuk Membangun History For Life - Huda, Khoirul; Feriandi, Yoga Ardian (Universitas Muhammadiyah Ponorogo, 2018)
This article aims to conduct studies to build character history for life in the younger generation through conservation education of cultural heritage perspective combined with the syntax of contex-learn inquiry. The method used in this article is the lybrary reserach method in which the object studied in this study comes from books, notes, journals, transcripts, research reports and other documents that can be found and related to conservative learning, character, history, etc. the techniques used to collect data with documentation, the researchers identify the discourse of books, papers or articles, magazines, journals, newspapers, web (internet), or other information related to conservative learning, character, history or directly related to the title of writing. after the data collected then the data is analyzed to obtain conclusions, forms in descriptive analysis techniques. The conclusion of this research indicates the importance to immediately apply conservation education in changing mindset and behavior in order to form character history for life especially for the young generation. Given the life of the era of globalization requires a young generation of the future that has three characteristics of knowledge or knowledge society, cultured or cultured society, and civilized or civilized society.